Evaluating the effect of infill compressive strength on the progressive collapse process of steel frames - Pouria Chavoshani, Ebrahim Khalilzadeh Vahidi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Structural safety has always been a key principle for designer engineers. One of the issues that structural engineers have been considered in recent decades is progressive collapse. Investigating the progressive collapse have become more important in a situation where terrorist attacks on civilian places and facilities are on the rise and buildings are increasingly exposed to the impact of explosions, collisions with vehicles, etc., requiring special attention and consideration. Accordingly, it is necessary to evaluate the factors affecting the progressive collapse in the operation of structures. One of the factors influencing the behavior of structures is masonry infills, which only their weight is considered in designing. The present study aimed to investigate the effect of compressive strength of infills on the progressive collapse process of 2-10 floor steel frames and compare their results with infill-free frames. The process of progressive collapse is performed by alternate path method and losing the middle floor column in OpenSees software. The results indicated that the addition of each MPa to the infill compressive strength will increase by about 33% and also the addition of each floor to the existing floors will increase the strength of the frame about 83%. Then, a relationship is proposed to determine the final strength of the frame based on infill’s compressive strength changes and the number of floors. In this regard, the proposed relationship in all cases has a maximum error of 5%.